KUALITAS PELAYANAN TOUR LEADER PT WEHA JALAN JALAN - Kevin Muhammad Irsyad; Rizki Nurul Nugraha (Media Bina Ilmiah, 2024)
In the era of globalization, services or products that compete in a market are growing rapidly. Companies that are able to compete are companies that provide quality products or services. This study aims to analyze service quality to increase customer satisfaction of PT Weha Jalan Jalan, a travel service company. A descriptive qualitative approach with SWOT analysis was used to identify strengths, weaknesses, opportunities, and threats related to service quality. Data were collected through observation, interviews, and literature study. SWOT analysis uses IFAS and EFAS matrix to evaluate the company's internal and external factors. The results showed that PT Weha Jalan Jalan's service quality is quite good based on customers' positive assessment of tangible, empathy, responsiveness, reliability, and assurance. SWOT analysis also revealed that PT Weha Jalan Jalan is in a strong position and has many opportunities to grow.